Effects of emotional labor on musculoskeletal disorders among physical therapists in Seoul - Choi, Jae Kwang; Lee, Yeon Hwan (International Journal of Occupational Safety and Health, 2023)
Introduction: Health care workers, including physical therapists, have some of the most important roles in the health care system as shown during the COVID-19 pandemic. Physical therapists encounter emotionally and physically vulnerable patients, experience emotional labor, and are exposed to conditions that can lead to job stress and musculoskeletal disorders. We aimed to examine the relationship between physical therapists’ emotional labor and its effect on perceived job stress and risk of musculoskeletal disorders.Methods: We conducted a 30-day survey among 230 physical therapists working in various settings from October 2 to November 1, 2019. Questionnaires, including questions on musculoskeletal symptoms, perceived job stress, and emotional labor, were administered to the participants.Results: The physical therapist's surface behavior affected the body burden. Job burnout experienced by physical therapists had an effect on their interpersonal relationships. The physical therapist's emotional law affects the degree of compensation.Conclusion: To prevent the long-term consequences of work-related strain, physical therapists should receive support in terms of maintaining a healthy lifestyle and developing effective methods of communication with patients. Encouragement of activities for psychological rejuvenation with colleagues with whom they can share emotional difficulties is also desirable. It is also necessary to establish a communication channel that can directly convey the grievances of physical therapists to hospitals.